Buenos Aires - McGarvey, Declan; Schultz, Jonathan; Gale Group (New York, New York DK Publishing, 2015)
Provides background information on Buenos Aires, Argentina; recommends the 10 best restaurants, nightlife, entertainment, hotels, and local attractions.
Buenos Aires' top 10 -- Around town -- Streetsmart.
"Your guide to the 10 best of everything"--Cover.
Includes indexes.
Keywords: Buenos Aires (Argentina) -- Guidebooks